Ag nanoparticle-decorated CoS nanosheet nanocomposites: a high-performance material for multifunctional applications in photocatalysis and supercapacitors. Issue 60 (8th June 2016) - Xu, Qing; Jiang, Deli; Wang, Tianyong; Meng, Suci; Chen, Min
Abstract : A novel Ag/CoS nanocomposite has been successfully synthesized by attaching Ag nanoparticles on the surface of CoS nanosheets with the assistance of light illumination. Abstract : A novel Ag/CoS nanocomposite has been successfully synthesized by attaching Ag nanoparticles on the surface of CoS nanosheets with the assistance of light illumination. The photocatalytic activity of the prepared Ag/CoS photocatalysts was evaluated by the decomposition of methylene blue (MB) under visible light. The composites exhibited enhanced photocatalytic activities compared with the pure CoS nanosheets and the 2 wt% Ag/CoS composite showed the best performance, which was 2 times higher than pristine CoS. It was illustrated that the improved photocatalytic activity of Ag/CoS photocatalysts mainly stems from the elevated charge separation efficiency caused by surface plasmon resonance of Ag nanoparticles. Furthermore, the Ag/CoS supercapacitor electrode showed a high capacitance of 370 F g −1 at a current density of 1 A g −1 in 1 M KOH aqueous electrolyte. The electrode exhibited excellent cyclic stability after 1000 cycles at 10 A g −1 current density. This work can be helpful for the exploration of plasmonic photocatalysts with enhanced photocatalytic activity and higher capacitance performance.